Duplex Ultrasound Evaluation of Portal Vein Congestion Index as a Predictor of Esophageal Varices: A Cross- sectional Study (Journal of Comilla Medical College Teachers' Association, 2025)
Background: The assessment of esophageal varices is critical in managing patients with portal hypertension, particularly those with liver cirrhosis. Duplex ultrasound offers a non-invasive method to evaluate portal hemodynamics, including the portal vein congestion index (PVCI), which is defined as the ratio of the cross-sectional area of the portal vein to the portal vein velocity.Objectives: The aim of the study was to evaluate the duplex ultrasound evaluation of portal vein congestion index as a predictor of esophageal varices.Methods: This cross-sectional study was conducted in the Department of Radiology & Imaging, Dhaka Medical College Hospital, Dhaka, from July 2021 to June 2023. Duplex study was done on 58 patients known case of cirrhosis of liver patients who attended the outpatient department or indoor of department of Dhaka Medical College Hospital, Dhaka. Statistical analyses of the results were be obtained by using window-based Microsoft Excel and Statistical Packages for Social Sciences (SPSS-24).Results: According to age, the majority of the study participants (17, 29.3%) were between the ages of 40 and 49, with 77.60% being male. The congestion index demonstrated a significant correlation with the presence of EV on EGD (p